Biochemical and haematological responses to thermal stress in Labeo rohita (Hamilton, 1822) fingerlings - Kumar, Prem; Pal, Asim K.; Sahu, Narottam P.; Christina, L.; Jha, Ashish Kumar (Indian Journal of Fisheries, 2019)
An experiment was conducted to understand the effect of thermal shock on stress and recovery in Labeo rohita (Hamilton, 1822) fingerlings. L. rohita fingerlings were exposed to a temperature of 380C for Â 2 h and permitted to recuperate afterwards for 48 h. Primary and secondary stress parameters were analysed after 2, 4, 8, 12, 24 and 48 h of recovery. The activity of glucose-6-phosphate dehydrogenase and acetylcholine esterase reduced significantly (p